Association of plasma biomarkers of fruit and vegetable intake with incident type 2 diabetes: EPIC-InterAct case-cohort study in eight European countries - Zheng, J-S; Sharp, SJ; Imamura, F; Papier, K; Tong, T; Et al. (BMJ Publishing Group, 2020)
Objective To investigate the association of plasma vitamin C and carotenoids, as indicators of fruit and vegetable intake, with the risk of type 2 diabetes.